Influência da aplicação local de bisfosfonato na osseointegração de implantes de titânio instalados em tíbia de coelho - Guimarães, Magáli Beck (2014)
The aim of this study was to make a comparative analysis of aspects related to the osseointegration of titanium implants placed with and without local application of a bisphosphonate, after 4 weeks, in vivo. The study comprised the placement of 50 cp. titanium implants in the middle third of the tibia of 10 rabbits, with the right tibia being used as control, and the left as test site. In the test group, local administration of sodium alendronate gel was instituted, and in the control group, sterile saline solution was used. After euthanasia, 10 implants from each group were analyzed for maximum removal torque. The remainder of the sample was processed to obtain non decalcified slides with approximately 30μm thick, in which histomorphological and histomorphometric analyses of bone-implant contact (%BIC) were performed. Data were analyzed at a level of significance of 5%. The removal torque of the test group, on an average, were half of the values obtained in the control group. The test group showed lower percentage of BIC, and notable changes in bone quality. It was concluded that the initial events of osseointegration of titanium implants are not favored by the local application of sodium alendronate gel in rabbits.